Autism Spectrum Disorder: The Impact of Stressful and Traumatic Life Events and Implications for Clinical Practice. - Fuld, Samantha (Clinical Social Work Journal, 2018)
Research findings suggest that behavioral interventions are effective in improving educational outcomes and fostering skill development in people with autism spectrum disorder (ASD). However, high rates of comorbidity between ASD and other psychological disorders, including depression and anxiety, indicate that standard behavioral approaches are not adequately addressing issues related to mental health in this population. Research emerging since the publication of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) is advancing our understanding of the nature of childhood stress and trauma in people with ASD and its subsequent impact on mental health and wellbeing. Mounting evidence for stress and trauma as a risk factor for comorbidity and the worsening of core ASD symptoms may intimate a shift in the way clinical social workers and other clinical practitioners conceptualize and approach work with this population to include trauma-focused assessment strategies and clinical interventions. Future directions for research to better understand the nature of childhood stress and trauma and improve mental health in this population are also discussed.